Epigenetic Variation May Compensate for Decreased Genetic Variation with Introductions: A Case Study Using House Sparrows (Passer domesticus) on Two Continents. (9th February 2012) - Schrey, Aaron W.; Coon, Courtney A. C.; Grispo, Michael T.; Awad, Mohammed; Imboma, Titus; McCoy, Earl D.; Mushinsky, Henry R.; Richards, Christina L.; Martin, Lynn B.
Abstract : Epigenetic mechanisms impact several phenotypic traits and may be important for ecology and evolution. The introduced house sparrow ( Passer domesticus ) exhibits extensive phenotypic variation among and within populations. We screened methylation in populations from Kenya and Florida to determine if methylation varied among populations, varied with introduction history (Kenyan invasion <50 years old, Florida invasion ~150 years old), and could potentially compensate for decrease genetic variation with introductions. While recent literature has speculated on the importance of epigenetic effects for biological invasions, this is the first such study among wild vertebrates. Methylation was more frequent in Nairobi, and outlier loci suggest that populations may be differentiated. Methylation diversity was similar between populations, in spite of known lower genetic diversity in Nairobi, which suggests that epigenetic variation may compensate for decreased genetic diversity as a source of phenotypic variation during introduction. Our results suggest that methylation differences may be common among house sparrows, but research is needed to discern whether methylation impacts phenotypic variation.